Fairness and the EC budget: Is Spain tilting at windmills? - Roger Bowles; Philip Jones (Intereconomics, 1991)
The poorer member states of the EC are often disappointed at what they see as a very limited degree of redistribution of resources away from the richer members towards the less well off. In a recent paper to the intergovernmental conference (IGC) on political union, for example, Spain calls for a number of measures, including explicit inter-state budget transfers, in order to increase the rate of convergence of income levels across member states. The purpose of this paper is to review the degree of redistribution entailed by the EC budget system as it works at present and to make some conjectures about the implications of pursuing the Spanish argument.
Keywords: 330; European Community